2012
DOI: 10.1590/s0103-50532012005000001
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of lycopene, β-carotene, retinol and α -tocopherol in plasma after a simple extraction procedure: stability study and application to human volunteers

Abstract: Um método para quantificação simultânea de licopeno, β-caroteno, retinol e α-tocoferol por cromatografia líquida de alta eficiência (HPLC) com detecção no visível/fluorescente e eluição isocrática foi otimizado e validado. O método consiste de extração líquido-líquido rápida e simples e posterior quantificação do sobrenadante extraído por HPLC. Alíquotas de plasma foram estocadas a -20°C por três meses para estudo da estabilidade. Aplicação metodológica foi realizada em amostras fornecidas por pintores e indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
8
2
Order By: Relevance
“…It is known that the main sources of β-carotene are fruits and vegetables, and a previous study conducted in the same region revealed that the consumption of this type of food is much higher in the RS when compared to the DS 1 , which is consistent with the interseasonal pattern we found. Unlike those of plasma β-carotene, the levels of lycopene were higher in the DS, with mean levels found in both seasons lower than in other studies with other populations all over the world 34,35 , and even from studies with other Brazilians living in the southern region 17,25 . Plasma carotenoids levels found in this study are in good agreement with the lower limit found for North American populations 35 .…”
Section: ▄ Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…It is known that the main sources of β-carotene are fruits and vegetables, and a previous study conducted in the same region revealed that the consumption of this type of food is much higher in the RS when compared to the DS 1 , which is consistent with the interseasonal pattern we found. Unlike those of plasma β-carotene, the levels of lycopene were higher in the DS, with mean levels found in both seasons lower than in other studies with other populations all over the world 34,35 , and even from studies with other Brazilians living in the southern region 17,25 . Plasma carotenoids levels found in this study are in good agreement with the lower limit found for North American populations 35 .…”
Section: ▄ Discussioncontrasting
confidence: 74%
“…Interestingly, the population's RS plasma β-carotene levels are substantially higher than those currently found in other populations 13,34 , and even in other Brazilian areas 17,25 . During the dry season, plasma β-carotene levels drop considerably but still remain in the safe range (>0.30μM/L) recommended by WHO 24 .…”
Section: ▄ Discussioncontrasting
confidence: 53%
See 3 more Smart Citations